Metaphor and Metonymy in Euphemisms in Queen Elizabeth II’s Official Statements - Janićijević, Marko M.; Gorčević, Admir R. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Though well recognised as devices used in the formation of euphemisms, metaphor and metonymy as such remain under-researched in current literature. Our study examines the use of euphemistic language in the official speeches and statements of the former British monarch, Queen Elizabeth II. The goal is to identify euphemisms and explain the metaphors and metonymies used in their formation, drawing on the Conceptual Metaphor and Metonymy Theory and Critical Metaphor Analysis. Metaphor and metonymy account for the formation of most of the analysed euphemisms. We argue that the analysed metaphors are motivated by the ideological concepts of (a) the struggle for survival and (b) materialism, as well as by the intent to positively evaluate certain political and everyday endeavours. The analysed metonymies are motivated by the intent to highlight more desirable or less undesirable aspects of events and things.
Keywords: euphemisms; metaphor; metonymy; political discourse; critical metaphor analysis